The implementation of the educational function of the familyduring three different eras – introduction to the subject issues - Dolata, Dorota (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
Nowadays, the education process becomes more flexible, and in connection withintense socio-cultural changes, more and more difficult to implement. Certainly this isdue to the dynamics of life of the members of the family system who, instead of witheach other, increasingly live side by side, fulfilling themselves in the professional level,but not always in a personal level. But this has not always been so. As a result, the objectiveof this article is to introduce the problems of evaluating the importance andpractice of the educational process in families over the pre-industrial, industrial andpost-industrial era, and show the result of its strong ties with the socio-cultural and economicprocesses, which were current at that time and are currently today too
Keywords: education process; educator; pupil; family; the present day